2022
DOI: 10.1002/pc.26784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkali surface treatment and compatibilizer agent on tensile and morphological properties of date palm fibers‐based high density polyethylene biocomposites

Abstract: The objective of the present study is to develop an environment friendly alternative material based on available and local bio‐source from the wastes of Algerian date palm trees, date palm twigs fiber (DPF) was selected as an effective reinforcing material for high density polyethylene (HDPE) biocomposite. Two types of treatments have been used including sodium hydroxide (NaOH) treatment to obtain DPF1 followed by potassium permanganate (KMnO4) treatment to obtain DPF2 for aim to improve fiber‐matrix compatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The author with the highest number of publications was Jawaid, M. He started the studies regarding the term "Biocomposite" in 2012 and published the first research under the tittle: A review of oil palm biocomposites for furniture design and applications: potential and challenges (Suhaily et al, 2012), being a reference in the subject "Biocomposite" with 359 publications. His last publication on the platform is entitled: Effect of alkali surface treatment and compatibilizer agent on tensile and morphological properties of date palm fibers-based high density polyethylene biocomposites (Hachaichi et al, 2022).…”
Section: Current Scenario On Biocomposites Publicationsmentioning
confidence: 99%
“…The author with the highest number of publications was Jawaid, M. He started the studies regarding the term "Biocomposite" in 2012 and published the first research under the tittle: A review of oil palm biocomposites for furniture design and applications: potential and challenges (Suhaily et al, 2012), being a reference in the subject "Biocomposite" with 359 publications. His last publication on the platform is entitled: Effect of alkali surface treatment and compatibilizer agent on tensile and morphological properties of date palm fibers-based high density polyethylene biocomposites (Hachaichi et al, 2022).…”
Section: Current Scenario On Biocomposites Publicationsmentioning
confidence: 99%
“…It is also possible to find the presence of crackles on the surface of the granules, which is probably due to extraction processes. Both types of fiber, from borlotti beans and green beans, respectively, were treated independently under the same extraction protocol [11]. Absorbed water was removed through freeze-drying because of the greater hygroscopicity of green bean fibers.…”
Section: Analyses Of Fibers: Chemical Fractionation and Characterizat...mentioning
confidence: 99%
“…The C-H stretching mode at 2930 cm −1 is characteristic of cellulose and hemicellulose. Also, the absorption band centered at 2889 cm −1 is characteristic of hemicellulose vibrational Both types of fiber, from borlotti beans and green beans, respectively, were treated independently under the same extraction protocol [11]. Absorbed water was removed through freeze-drying because of the greater hygroscopicity of green bean fibers.…”
Section: Analyses Of Fibers: Chemical Fractionation and Characterizat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Li [33] found that adding a coupling agent (MAPE) enhanced the flexural and tensile properties of wood/HDPE composites and improved the interfacial adhesion, as evidenced by the SEM micrographs. Hachaichi et al [34] recently studied the effects of alkali surface modification and a compatibilizer agent on HDPE's mechanical behavior and microstructure reinforced with date palm fiber (DPF) biocomposites. The results indicated that incorporating 30 wt% of DPF treated with NaOH and KMnO4 (DPF2) in the HDPE biocomposite improved the mechanical and morphological properties.…”
Section: Introductionmentioning
confidence: 99%